Prognostic impact of selection criteria of current adjuvant endocrine therapy trials NATALEE and monarchE in postmenopausal HRpos/HER2neg breast cancer patients treated with upfront letrozole - Fasching, Peter Andreas; Hack, Carolin Christine; Nabieva, Naiba; Maass, Nicolai; Aktaş, Bahriye; Kümmel, Sherko; Thomssen, Christoph; Wolf, Christopher; Kolberg, Hans-Christian; Brucker, Cosima; Janni, Wolfgang; Dall, Peter; et al. (European journal of cancer, 2024)
Background - The monarchE and NATALEE trials demonstrated the benefit of CDK4/6 inhibitor (CDK4/6i) therapy in adjuvant breast cancer (BC) treatment. Patient selection, based on clinical characteristics, delineated those at high (monarchE) and high/intermediate recurrence risk (NATALEE). This study employed a historical patient cohort to describe the proportion and prognosis of patients eligible for adjuvant CDK4/6i trials. - Methods - Between 2009 and 2011, 3529 patients were enrolled in the adjuvant PreFace clinical trial (NCT01908556). Eligibility criteria included postmenopausal patients with hormone receptor-positive (HRpos) BC for whom a five-year upfront therapy with letrozole was indicated. Patients were categorized into prognostic groups according to monarchE and NATALEE inclusion criteria, and their invasive disease-free survival (iDFS) and overall survival (OS) were assessed. - Results - Among 2891 HRpos patients, 384 (13.3 %) met the primary monarchE inclusion criteria. The majority (n = 261) qualified due to having ≥ 4 positive lymph nodes. For NATALEE, 915 out of 2886 patients (31.7 %) met the eligibility criteria, with 126 patients (13.7 %) being node-negative. Patients from monarchE with ≥ 4 positive lymph nodes and NATALEE with stage III BC exhibited the poorest prognosis (3-year iDFS rate 0.87). Patients ineligible for the trials demonstrated prognoses similar to the most favorable patient groups within the eligibility criteria. - Conclusion - Patient populations eligible for monarchE and NATALEE trials differed. Nearly a third of the postmenopausal HRpos population, previously under upfront letrozole treatment, met the NATALEE prognostic eligibility criteria. As certain eligible groups had a prognosis similar to non-eligible patients, it might be interesting to explore additional patient groups for CDK4/6i therapy.